Magnetic field dependent interactions in an ultracold Li–Yb(3P2) mixture - William Dowd; Richard J Roy; Rajendra K Shrestha; Alexander Petrov; Constantinos Makrides; Svetlana Kotochigova; Subhadeep Gupta (New Journal of Physics, 2015)
Magnetic Feshbach resonances have allowed great success in the production of ultracold diatomic molecules from bi-alkali mixtures, but have so far eluded observation in mixtures of alkali and alkaline-earth-like atoms. Inelastic collisional properties of ultracold atomic systems exhibit resonant behavior in the vicinity of such resonances, providing a detection signature. We study magnetic field dependent inelastic effects via atom loss spectroscopy in an ultracold heteronuclear mixture of alkali ^6 Li in the ground state and alkaline-earth-like ^174 Yb in an excited electronic metastable state ( ^3 P _2 , ${{m}_{J}}=-1$ ). We observe a variation of the interspecies inelastic two-body rate coefficient by nearly one order of magnitude over a 100–520 G magnetic field range. By comparing to ab initio calculations we link our observations to interspecies Feshbach resonances arising from anisotropic interactions in this novel collisional system.